(untitled) (Bangladesh Medical Journal, 2016)
Endoscopic retrograde cholangio pancreaticogrphy (ERCP), though complex and invasive, is one of the commonly performed endoscopic procedures. Its benefits are sometimes compromised by complications which may be life threatening in some instances. Pancreatitis, bleeding, perforation, infections (cholangitis & cholecystitis) and sedation-related complications are common ERCP related complications. This prospective observational study was carried out in the department of Gastroenterology, BSMMU from September 2014 to December 2014 on 56 consecutive patients who underwent ERCP with the intention to assess the occurrence of different ERCP related complications. Nearly half of the patients (51.78%) in this study were suffering from obstructive jaundice due to malignant biliary obstruction. Thirty two percent (32 %) patients had stone in the common bile duct presenting with or without cholangitis. Total 9 patients developed complications and among them 5 patients developed cholangitis in the post ERCP period. Rest of the 2 patients developed pancreatitis. Patient related factors including underlying diagnosis together with variability in endoscopic settings and health care environments may be responsible for occurrence of complications and differences rate of complications across different institutions. Bangladesh Med J. 2015 May; 44 (2): 97-101